(untitled) (Islas, 2021)
En este texto se presenta la discusión que genera Paulette Dieterlen acerca de las implicaciones al momento de abordar el tema de la pobreza. Se problematiza el concepto de igualdad y justicia, así como las formulaciones que surgen del campo de la economía. A través de este recorrido, la intención del artículo es superar las limitantes de la medición universal de la pobreza que supone la economía y la macroeconomía, a través de una visión filosófica como lo es el campo de la ética. This text presents the discussion that Paulette Dieterlen generates about the implications when addressing the issue of poverty. The concept of equality and justice is problematized, as well as the formulations that emerge from the field of economics. Through this journey, the intention of the article is to overcome the limitations of the universal measurement of poverty that the economy and macroeconomics entail, through a philosophical vision such as the field of ethics.